Sistem Alat Pendeteksi Detak Jantung, Suhu Tubuh dan Tekanan Darah dengan Metode PID (Propotional Integral Derivative) - Yovi Afriansyah; Rahman Arifuddin; Yunus Novrianto (Universitas Merdeka Malang, 2021)
One of the important things in military education are three main models, namely academic, behavioral attitude and physical training. Of the three main samples, the non-commissioned officer cadet is obliged to fulfill it. Such as physical training and related activities provided during basic education and skills courses. In this study, a system was made to determine heart rate, body temperature and blood pressure using the PID method. This research aims to make this a tool so that the health care team, when implementing physical activity health support, can quickly and practically help people, especially TNI soldiers. The results showed that PID control is suitable for this tool as it results in significant changes. The resulting response matches the characteristics of the PID controller. The error value between DS18B20 temperature sensor and digital thermometer is 0.22%, for armpit measurement, the error value between pulse sensor and oximeter is 0.6%. Meanwhile, the error value between the MPX5050DP probe and the digital sphygmomanometer is 1.4%.